Reinforcement learning algorithm based on minimum state method and average reward - LIU Quan1; FU Qi-ming1; GONG Sheng-rong1; FU Yu-chen1; CUI Zhi-ming1 (Tongxin xuebao)
In allusion to the problem that Q-Learning,which was used discount reward as the evaluation criterion,could not show the affect of the action to the next situation,AR-Q-Learning was put forward based on the average reward and Q-Learning.In allusion to the curse of dimensionality,which meant that the computational requirement grew exponen-tially with the number of the state variable.Minimum state method was put forward.AR-Q-Learning and minimum state method were used in reinforcement learning for Blocks World,and the result of the experiment shows that the method has the characteristic of aftereffect and converges more faster than Q-Learning,and at the same time,solve the curse of di-mensionality in a certain extent in Blocks World.